التوجيه النحوي للقراءات القرآنية: نقد وتوجيه في ضوء لغات العرب - بن ساسي، بلقندوز; مذبوحي، محمد (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست - معهد الآداب واللغات, 2021)
يهدف الباحث إلى نقد توجيهات النحاة للقراءات القرآنية باستبعادهم لغات العرب، ثم يوجه القراءات القرآنية توجيهات لغوية في ضوء لغات العرب، وقد توج البحث بنتائج، أهمها:- إقرار وجود لغات متعددة تندرج تحت لسان واحد هو اللسان العربي.- ضرورة عزو كثير من اختلافات القراءات القرآنية إلى اختلافات في لغات العرب.
The Qur’anic readings have been in contradiction with several places of grammatical analogy. Thus, this was an obstacle to the progression of grammatical rules, so that grammarians were eager to orient Qur’anic readings which contradicted many standard and guidelines, to what extent did the grammarians guide Qur'anic readings according to their standard grammar, and take into account the different languages of the Arabs? The researcher aims to criticize grammarians directives of Qur’anic readings for excluding the languages of the Arabs, then he directs the Qur’anic readings by linguistic directives in the light of the languages of the Arabs. The research results are : the declaration of the existence of multiple languages that fall under one tongue, which is the Arabic tongue, the necessity of attributing many of the differences in Qur’anic readings to differences in the languages of the Arabs
Keywords: القرآن الكريم -- القراءات القرآنية -- التوجيه النحوي -- النقد الأدبي